2003
DOI: 10.1002/psc.504
|View full text |Cite
|
Sign up to set email alerts
|

Structure–antiviral activity relationships of cecropin A‐magainin 2 hybrid peptide and its analogues

Abstract: In order to elucidate the structure-antiviral activity relationship of cecropin A (1-8)-magainin 2 (1-12) (termed CA-MA) hybrid peptide, several analogues with amino acid substitutions were synthesized. In a previous study, it was shown that serine at position 16 in CA-MA hybrid peptide was very important for antimicrobial activity. Analogues were designed to increase the hydrophobic property by substituting a hydrophobic amino acid residue (S --> A, V, F or W, position 16) in the CA-MA hybrid peptide. In this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
25
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 21 publications
0
25
0
Order By: Relevance
“…Although assays were less sensitive for VEE, detection limits for VEE in the AMP-based assays were similar to or better than those of competing cell-or antibodybased technologies [21,22,24,25]. Several groups have previously described the antiviral effects of various AMPs and their derivatives on vaccinia virus [26][27][28]. Most relevant to the present study is a cecropin Amagainin-2 hybrid peptide (CA (1-8)-MA(1-12)) which was shown to exhibit antiviral effects in other studies [26].…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Although assays were less sensitive for VEE, detection limits for VEE in the AMP-based assays were similar to or better than those of competing cell-or antibodybased technologies [21,22,24,25]. Several groups have previously described the antiviral effects of various AMPs and their derivatives on vaccinia virus [26][27][28]. Most relevant to the present study is a cecropin Amagainin-2 hybrid peptide (CA (1-8)-MA(1-12)) which was shown to exhibit antiviral effects in other studies [26].…”
Section: Discussionmentioning
confidence: 93%
“…Several groups have previously described the antiviral effects of various AMPs and their derivatives on vaccinia virus [26][27][28]. Most relevant to the present study is a cecropin Amagainin-2 hybrid peptide (CA (1-8)-MA(1-12)) which was shown to exhibit antiviral effects in other studies [26]. The three cecropins (with identical sequences in the first 8 amino acids) exhibited varying affinities for vaccinia virus in the present study, thereby implicating the positions of charged residues and lengths of hydrophobic segments within the C-terminal sequences for these differences.…”
Section: Discussionmentioning
confidence: 99%
“…This is possibly due to the presence of hydrophobic amino acid residues, which might interact with the viral envelope and also with phospholipids encountered on the viral surface [65], [66]. Previous descriptions showed various antiviral peptides that presented directly proportional activity in relation to the hydrophobic ratio, suggesting that hydrophobic and aromatic residues are also important for antiviral activity.…”
Section: Discussionmentioning
confidence: 99%
“…However, major concerns about the use of cecropin A as a pesticide in plant protection are the high production cost of such a long peptide and its sensitivity to protease degradation. Searches for shorter, more potent, nontoxic, and more stable peptides have led to the identification of synthetic peptides with broader and higher activity than their natural counterparts (3,5,6,8,16,17,19,23,33,41,50). In particular, the 11-residue sequence WKLFKKI LKVL-NH 2 (Pep3), derived from the well-known cecropin A(1-7)-melittin(2-9) hybrid peptide (8,17,23), is sufficient for antifungal and antibacterial activities (4,16).…”
mentioning
confidence: 99%